Prevalence of osteoarthritis in individuals with COPD: a systematic review - Wshah, Adnan (Int J Chron Obstruct Pulmon Dis, 2018)
The objective of this review was to examine the prevalence of osteoarthritis (OA) in individuals with COPD. A computer-based literature search of CINAHL, Medline, PsycINFO and Embase databases was performed. Studies reporting the prevalence of OA among a cohort of individuals with COPD were included. The sample size varied across the studies from 27 to 52,643 with a total number of 101,399 individuals with COPD recruited from different countries. The mean age ranged from 59 to 76 years. The prevalence rates of OA among individuals with COPD were calculated as weighted means. A total of 14 studies met the inclusion criteria with a prevalence ranging from 12% to 74% and an overall weighted mean of 35.5%. Our findings suggest that the prevalence of OA is high among individuals with COPD and should be considered when developing and applying interventions in this population.